Automatic and human evaluation on English-Croatian legislative test set - Brkić, Marija; Vičić, Tomislav; Seljan, Sanja (2013)
This paper presents work on the manual and automatic evaluation of the online available machine translation (MT) service Google Translate, for the English-Croatian language pair in legislation and general domains. The experimental study is conducted on the test set of 200 sentences in total. Human evaluation is performed by native speakers, using the criteria of fluency and adequacy, and it is enriched by error analysis. Automatic evaluation is performed on a single reference set by using the following metrics: BLEU, NIST, F-measure and WER. The influence of lowercasing, tokenization and punctuation is discussed. Pearson's correlation between automatic metrics is given, as well as cor relation between the two criteria, fluency and adequacy, and automatic metrics.
ISBN 978-3-642-37246-9 ; 14th International Conference (CICLing 2013) "Computational Linguistics and Intelligent Text Processing" : proceedings. Part I ; Alexander Gelbukh (ur.) ; Samos, Grčka ; 24.-30.03.2013.
Projekt MZOS
ENG